Zebrafish Pax1a and Pax1b are required for pharyngeal pouch morphogenesis and ceratobranchial cartilage development. (March 2020) - Liu, Yu-Hsiu; Lin, Tz-Chi; Hwang, Sheng-Ping L.
Abstract: Pharyngeal arches are derived from all three germ layers and molecular interactions among the tissue types are required for proper development of subsequent pharyngeal cartilages; however, the mechanisms underlying this process are not fully described. Here we report that in zebrafish, Pax1a and Pax1b have overlapping and essential functions in pharyngeal pouch morphogenesis and subsequent ceratobranchial cartilage development. Both pax1a and pax1b are co-expressed in pharyngeal pouches, and time-lapse imaging of a novel Tg(pax1b:eGFP) enhancer trap line further revealed the sequential segmental development of pharyngeal pouches. Zebrafish pax1a −/− ; pax1b −/− double mutant embryos generated by CRISPR-Cas9 mutagenesis exhibit unsegmented pharyngeal pouches 2–5 with small outpocketings. Endodermal expression of fgf3, tbx1 and edn1 is also absent in pharyngeal pouches 2–5 at 36 h post fertilization (hpf). Loss of ceratobranchial cartilage 1–4 and reduced or absent expression of dlx2a and hand2 in the pharyngeal arches 3–6 are observed in CRISPR mutant and morphant embryos that are deficient in both zebrafish pax1a and pax1b at 96 or 36 hpf. These results suggest that zebrafish Pax1a and Pax1b both regulate pharyngeal pouch morphogenesis by modulating expression of fgf3 and tbx1 . Furthermore, our data support a model wherein endodermal Pax1a and Pax1b act through Fgf3 and Tbx-Edn1 signaling to non-autonomously regulate the development of ceratobranchial cartilage via expression of dlx2a and hand2 . Highlights: Pax1a and Pax1b regulate pharyngeal pouch morphogenesis by modulating expression of tbx1 and fgf3 . Pax1a and Pax1b non-autonomously regulate ceratobranchial cartilage formation. pax1b expression signifies the location of newly developing pouch before they migrate laterally.